Dynamics of infection and pathology induced by the aporocotylid, Cardicola laruei, in Spotted Seatrout, Cynoscion nebulosus (Sciaenidae). Issue 10 (September 2020) - McElroy, Eric J.; Nowak, Barbara; Hill-Spanik, Kristina M.; Granath, Willard O.; Connors, Vincent A.; Driver, Jim; Tucker, C. Jonathan; Kyle, Dennis E.; de Buron, Isaure
Graphical abstract: Highlights: Aporocotylid Cardicola laruei infects the heart of wild sciaenid Cynoscion nebulosus. Prevalence of infection by adult flukes (61%) and granulomas (84%) peak in summer. Female seatrout are infected by more flukes than males. Seatrout ventricle is damaged by epithelialized granulomas and blister-like extrusions through the epicardium. Granulomas may be used to translocate live Cardicola eggs as occurs in schistosomes. Abstract: The sciaenid Spotted Seatrout ( Cynoscion nebulosus ) are infected by blood flukes ( Cardicola spp.). A 2 year survey in estuaries of South Carolina, USA, showed that adult flukes and granulomas occurred throughout the year but their prevalence was highest in summer (61% and 84%, respectively), indicating an unusually high level of infection for wild fish. Granulomas remained after adult flukes could no longer be found. PCR-Restriction Fragment Length Polymorphism (RFLP) of a subsample of specimens allowed identification of Cardicola laruei as the only species infecting these seatrout during the period of study. Mean intensity of infection by flukes was higher in female seatrout, suggesting endocrine and/or immune system involvement. The prevalence of granulomas declined sharply in winter, indicating possible mortality of infected seatrout as this species is known to be cold-sensitive. Granulomas were studied using histology, immunohistochemistry, and transmission electron microscopy. Eggs were encapsulated by an inner core of dark epithelioid cells, and an outer core of large epithelioid cells undergoing epithelialization. Fibrosis was observed around granulomas and some granulomas detached from the surrounding damaged myocardium. Numerous inflammatory cells appeared mobilised around granulomas and pathology could be severe, in some cases showing grossly visible blister-like extrusions scattered in the damaged epicardium. At the gross level, some granulomas possessing eggs with live miracidia were observed at the surface of the epicardium. These findings suggest that granulomas carrying both dead and live eggs can clear the fish heart by host-mediated transport through the myocardium, as is known to occur in related human Schistosoma infections.